Formalizing natural languages with NooJ 2018 and its natural language processing applications : 12th International Conference, NooJ 2018, Palermo, Italy, June 20-22, 2018, Revised selected papers /: 12th International Conference, NooJ 2018, Palermo, Italy, June 20-22, 2018, Revised selected papers. (2019) - Unknown
No abstract available